Digital Image Watermarking in Discrete Fourier Transform domain - Jimson, Ningombam; Hemachandran, Kattamanchi (International Journal of Computer Sciences and Engineering, 2025)
The rapid development of internet communication has increased the rate at which digital data is being shared wideley as the digital data can be flawlessly copied and distributed over the internet. A Digital watermarking is a process in which a bit of information is added to the digital data like image video and audio. A CDMA based image watermarking method in Discrete Fourier Transform (DFT) is proposed in this paper for protecting the copyright and authentication of the digital image. The original digital image is divided into a non-overlapping block of 8X8 and one bit of binary information is embedded in the block using two highly uncorrelated Pseudo-random sequences in the coefficient of the magnitude domain of DFT. For watermark extraction, the original image is not required. Based on the correlation values between magnitude coefficient and Pseudo-random sequences the watermark is extracted from the watermarked image. The scheme is tested using Stimark Benchmarking tools. The Experimental result suggested that the method is robust against numbers of digital watermarking attacks.